Ontology after Ontotheology : Plurality, Event, and Contingency in Contemporary Philosophy - Heiden, Gert-Jan van der, 1976- (Book collections on Project MUSE., 2014)
"Van der Heiden works largely with present-day thinkers such as Badiou, Nancy, Romano, Meillassoux, and Agamben, and examines contemporary thought as it seeks to recover a sense of the absolute, but without recourse to specifically theological underpinnings"--